Packaging materials for paper containers and liquid paper containers

The packaging material for paper containers addresses heat-induced deterioration of aluminum oxide layers by optimizing layer thickness and composition, ensuring robust adhesion and maintaining barrier properties.

JP7604773B2Active Publication Date: 2024-12-24DAI NIPPON PRINTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019164644
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-10-24
Filing Date
2019-09-10
Publication Date
2024-12-24
Estimated Expiration
2039-09-10

AI Technical Summary

Technical Problem

Aluminum oxide-based transparent vapor-deposited layers in packaging materials for paper containers suffer from heat-induced deterioration due to their lower heat resistance compared to inorganic compounds like silicon oxide, leading to barrier deterioration.

Method used

A packaging material for paper containers is designed with multiple layers, including an outer and inner thermoplastic resin layer, a paper base layer, an adhesive resin layer, and a vapor-deposited film with a transparent vapor-deposited layer containing aluminum oxide, where the vapor-deposited film consists of a stretched plastic film and a gas barrier coating film, and the adhesive resin layers are optimized in thickness and composition to enhance adhesion and heat resistance.

Benefits of technology

The solution effectively suppresses heat-induced deterioration of the aluminum oxide layer, maintaining the barrier properties of the packaging material and enhancing its adhesion to the paper base, thereby improving the durability and performance of the packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604773000002
    Figure 0007604773000002
  • Figure 0007604773000003
    Figure 0007604773000003
  • Figure 0007604773000004
    Figure 0007604773000004
Patent Text Reader

Abstract

To prevent the properties of a transparent vapor deposition layer containing aluminum oxide from deteriorating due to heat.SOLUTION: A packaging material for paper container at least has, in order from outside to inside, an outer thermoplastic resin layer, a paper substrate layer, an adhesion resin layer, a vapor deposition film, an adhesion layer, and an inner thermoplastic resin layer. The vapor deposition film has a stretched plastic film, a transparent vapor deposition layer provided on the stretched plastic film and containing aluminum oxide, and a gas barrier coating film provided on the transparent vapor deposition layer. The stretched plastic film of the vapor deposition film has biomass-derived polyester. The adhesion resin layer has an inside adhesion resin layer positioned on the vapor deposition film side, and an outside adhesion resin layer positioned on the paper substrate layer side.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid paper container that contains liquid and a packaging material for constituting the liquid paper container. [Background technology]

[0002] Polyesters are widely used in various industrial applications because they are inexpensive and have excellent mechanical properties, chemical stability, heat resistance, and transparency. Polyesters are obtained by polycondensation of diol units and dicarboxylic acid units. For example, polyethylene terephthalate (hereinafter sometimes abbreviated as PET) is produced by esterifying ethylene glycol and terephthalic acid as raw materials and then polycondensing them. These raw materials are produced from petroleum, a fossil resource. For example, ethylene glycol is industrially produced from ethylene, and terephthalic acid is industrially produced from xylene.

[0003] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field, just as there is in energy, and the use of biomass has attracted attention. Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and by using it, it becomes carbon dioxide and water again, making it a so-called carbon-neutral renewable energy. Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and there are also attempts to produce polyester, a general-purpose polymer material, from these biomass raw materials.

[0004] As a polyester made from biomass raw materials, polyester made from isosorbide, one of the biomass raw materials, terephthalic acid, and ethylene glycol is known. For example, Patent Document 1 proposes constructing a liquid paper container for containing liquid using a packaging material containing biomass polyester (hereinafter simply referred to as "biomass polyester") made from ethylene glycol derived from biomass. The packaging material of Patent Document 1 includes a base layer whose main component is polyester made from diol units and dicarboxylic acid units containing ethylene glycol derived from biomass, and a paper base layer bonded to the base layer. A transparent deposition layer made of aluminum oxide is formed on the base layer by physical vapor deposition. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-36208 A Summary of the Invention [Problem to be solved by the invention]

[0006] Aluminum oxide has lower heat resistance than inorganic compounds such as silicon oxide, which are examples of other materials constituting the transparent vapor-deposited layer, and therefore the heat generated when adhering a vapor-deposited film having a transparent vapor-deposited layer containing aluminum oxide to a paper base layer may cause the barrier degradation of the transparent vapor-deposited layer containing aluminum oxide.

[0007] An object of the present invention is to provide a packaging material for paper containers that can effectively solve these problems. [Means for solving the problem]

[0008] The present invention is a packaging material for paper containers comprising, in order from outside to inside, at least an outer thermoplastic resin layer, a paper base material layer, an adhesive resin layer, a vapor deposition film, an adhesive layer, and an inner thermoplastic resin layer, in which the vapor deposition film has a stretched plastic film, a transparent vapor deposition layer containing aluminum oxide and provided on the stretched plastic film, and a gas barrier coating film provided on the transparent vapor deposition layer, the stretched plastic film of the vapor deposition film contains biomass-derived polyester, and the adhesive resin layer comprises an inner adhesive resin layer located on the vapor deposition film side, and an outer adhesive resin layer located on the paper base material layer side.

[0009] In the packaging material for paper containers according to the present invention, the thickness of the inner adhesive resin layer is preferably thinner than the thickness of the outer adhesive resin layer.

[0010] The packaging material for paper containers according to the present invention may further comprise an anchor coat layer located between the inner adhesive resin layer and the vapor-deposited film.

[0011] In the packaging material for paper containers according to the present invention, it is preferable that the thickness of the adhesive resin layer is 25 μm or more and 60 μm or less, and the thickness of the inner adhesive resin layer of the adhesive resin layer is 10 μm or more and less than 25 μm.

[0012] In the packaging material for paper containers according to the present invention, the transparent vapor deposition layer of the vapor deposition film may be provided on the inner surface of the stretched plastic film, or the transparent vapor deposition layer of the vapor deposition film may be provided on the outer surface of the stretched plastic film.

[0013] In the packaging material for paper containers according to the present invention, the transparent vapor deposition layer includes a transition region, which is a region between the position of the peak of elemental bond Al2O4H that is transformed into aluminum hydroxide, detected by etching the vapor deposition film from the gas barrier coating film side using time-of-flight secondary ion mass spectrometry (TOF-SIMS), and the interface between the transparent vapor deposition layer and the stretched plastic film, and the ratio of the thickness of the transition region to the thickness of the transparent vapor deposition layer may be 5% or more and 60% or less.

[0014] In the packaging material for paper containers according to the present invention, the outer thermoplastic resin layer or the inner thermoplastic resin layer may contain biomass-derived polyethylene.

[0015] The present invention is a liquid paper container made from the above-described paper container packaging material. Effect of the Invention

[0016] According to the present invention, it is possible to suppress deterioration of the characteristics of a transparent vapor-deposited layer containing aluminum oxide due to heat. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a packaging material according to the present embodiment. [Diagram 2] FIG. 11 is a cross-sectional view showing a modified example of the packaging material according to the present embodiment. [Diagram 3] FIG. 11 is a cross-sectional view showing a modified example of the packaging material according to the present embodiment. [Figure 4] FIG. 11 is a cross-sectional view showing a modified example of the packaging material according to the present embodiment. [Diagram 5] FIG. 13 is a diagram showing an example of the results of analyzing a transparent vapor deposition layer using a time-of-flight secondary ion mass spectrometer. [Figure 6] FIG. 1 is a diagram showing an example of a film forming apparatus for forming a transparent vapor deposition layer on a stretched plastic film. [Figure 7]2 is a cross-sectional view showing an example of a laminate obtained by laminating a vapor-deposited film with an inner thermoplastic resin layer and an inner adhesive resin layer. FIG. [Figure 8] FIG. 2 is a diagram showing an example of a lamination device for laminating a laminate having a vapor-deposited film, an inner thermoplastic resin layer, and an inner adhesive resin layer onto a paper base layer. [Figure 9] FIG. 2 is a perspective view showing an example of a liquid paper container. [Figure 10A] FIG. 1 is a diagram showing the evaluation results of Examples A1 to A3. [Figure 10B] FIG. 1 is a diagram showing the evaluation results of Reference Examples A1 to A5. [Figure 11] FIG. 2 is a diagram showing the layer structures of packaging materials for paper containers in Examples B1 to B3 and Comparative Examples B1 to B2. [Figure 12] FIG. 1 is a diagram showing the measurement results of peel strength, water vapor permeability, and oxygen permeability. [Figure 13] FIG. 1 is a diagram showing the evaluation results of the sealing property of a filling machine. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In the present invention, "biomass polyester" and "stretched plastic film containing biomass polyester" mean that at least a portion of the raw materials used are derived from biomass, but do not mean that all of the raw materials are derived from biomass.

[0019] <Packaging materials> A paper container packaging material 10 according to the present embodiment will be described with reference to the drawings.

[0020] FIG. 1 is a cross-sectional view showing an example of a packaging material according to the present embodiment. The paper container packaging material 10 shown in FIG. 1 includes, from outside to inside, at least an outer thermoplastic resin layer 11, a paper base layer 12, an adhesive resin layer 13, a vapor deposition film 14, an adhesive layer 15, and an inner thermoplastic resin layer 16. In a liquid paper container including the paper container packaging material 10 shown in FIG. 1, the inner thermoplastic resin layer 16 constitutes the inner surface (hereinafter also referred to as the inner surface) 10x of the liquid paper container. The outer thermoplastic resin layer 11 constitutes the outer surface (hereinafter also referred to as the outer surface) 10y of the liquid paper container. The "inner surface" refers to the side located closer to the inside of the liquid paper container when the paper container packaging material 10 constitutes a liquid paper container, and the "outer surface" refers to the side located closer to the outside of the liquid paper container.

[0021] 1, the deposited film 14 has a stretched plastic film 141, a transparent deposited layer 142 containing aluminum oxide provided on the inner surface of the stretched plastic film 141, and a gas barrier coating film 143 provided on the transparent deposited layer 142. The adhesive resin layer 13 includes an inner adhesive resin layer 131 located on the deposited film 14 side, and an outer adhesive resin layer 132 located on the paper base layer 12 side. The stretched plastic film 141 of the deposited film 14 is in contact with the inner adhesive resin layer 131, and the gas barrier coating film 143 of the deposited film 14 is in contact with the adhesive layer 15.

[0022] In addition to the above layers, the paper container packaging material 10 may further include a printed layer, etc. For example, the outer thermoplastic resin layer 11 may be provided with a printed layer.

[0023] Fig. 2 is a cross-sectional view showing a modified example of the packaging material according to the present embodiment. The example in Fig. 2 is the same as the paper container packaging material 10 shown in Fig. 1 except that the paper container packaging material 10 further includes an anchor coat layer 17 located between the inner adhesive resin layer 131 and the vapor deposition film 14.

[0024] Fig. 3 is a cross-sectional view showing a modified example of the packaging material according to the present embodiment. The example in Fig. 3 is different only in that a transparent vapor deposition layer 142 of a vapor deposition film 14 is provided on the outer surface of a stretched plastic film 141, and the other configurations are the same as those of the paper container packaging material 10 shown in Fig. 1. In the example shown in Fig. 3, a gas barrier coating film 143 of the vapor deposition film 14 contacts the inner adhesive resin layer 131, and a stretched plastic film 141 of the vapor deposition film 14 contacts the adhesive layer 15.

[0025] Fig. 4 is a cross-sectional view showing a modified example of the packaging material according to the present embodiment. The example in Fig. 4 is the same as the paper container packaging material 10 shown in Fig. 3 except that the paper container packaging material 10 further includes an anchor coat layer 17 located between the inner adhesive resin layer 131 and the vapor deposition film 14.

[0026] The films and layers that make up the paper container packaging material 10 will be described below.

[0027] [Thermoplastic resin layer] The outer thermoplastic resin layer 11 and the inner thermoplastic resin layer 16 can be formed using a thermoplastic resin that can be melted and fused to each other by heat. Examples of the thermoplastic resin include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymer polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, methylpentene polymer, polybutene polymer, acid-modified polyolefin resin obtained by modifying a polyolefin resin such as polyethylene or polypropylene with an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, or itaconic acid, polyvinyl acetate resin, poly(meth)acrylic resin, and polyvinyl chloride resin. Low-density polyethylene, linear low-density polyethylene, and ethylene-α-olefin copolymer polymerized using a metallocene catalyst are preferably used.

[0028] The thermoplastic resin of the outer thermoplastic resin layer 11 and the inner thermoplastic resin layer 16 may contain a material derived from biomass or may contain a material derived from fossil fuel. When the thermoplastic resin layer contains a material derived from biomass, it may contain a biomass polyolefin, which is a polymer of a monomer containing ethylene derived from biomass. Since ethylene derived from biomass is used as the raw material monomer, the polymerized polyolefin is derived from biomass. The content of ethylene derived from biomass in the raw material monomer does not need to be 100% by mass, and is, for example, preferably 50% or more, more preferably 80% or more. The raw material monomer may contain ethylene derived from fossil fuel, or may contain α-olefin monomers such as butylene, hexene, and octene. Even in such a case, the obtained polymer is called biomass polyethylene. By containing α-olefin, the polymerized polyolefin has an alkyl group as a branched structure, and therefore can be more flexible than a simple linear one.

[0029] Biomass-derived ethylene can be produced using biomass-derived ethanol as a raw material. In particular, it is preferable to use biomass-derived fermented ethanol obtained from a plant raw material. The plant raw material is not particularly limited, and any conventionally known plant can be used. Examples of the plant raw material include corn, sugarcane, beet, and manioc.

[0030] Fermented ethanol derived from biomass refers to ethanol produced by contacting a culture solution containing a carbon source obtained from a plant raw material with an ethanol-producing microorganism or a product derived from its crushed material, and then purifying the ethanol. Conventionally known methods such as distillation, membrane separation, and extraction can be used to purify ethanol from the culture solution. For example, methods include adding benzene, cyclohexane, etc., and removing water by azeotropy or membrane separation.

[0031] Linear low-density polyethylene is obtained by polymerizing ethylene and a small amount of α-olefins using a low-pressure polymerization method (gas phase polymerization using a Ziegler-Natta catalyst or liquid phase polymerization using a metallocene catalyst). Low-density polyethylene is also obtained by polymerizing ethylene using a high-pressure polymerization method. Linear low-density polyethylene has many short molecular chains in its molecular chains and has excellent sealing performance.

[0032] Linear low density polyethylene and low density polyethylene have a viscosity of 0.89 g / cm 3 More than 0.93g / cm 3 Less than or equal to 0.90 g / cm 3 More than 0.925g / cm 3 The density of linear low density polyethylene is 0.89 g / cm or less. The MFR of linear low density polyethylene may be lower than the MFR of low density polyethylene. The density of linear low density polyethylene and low density polyethylene is a value measured according to the method specified in Method A of JIS K7112-1980 after annealing as specified in JIS K6760-1995. When the density of linear low density polyethylene and low density polyethylene is 0.89 g / cm or less, the density of linear low density polyethylene and low density polyethylene is 0.89 g / cm or less. 3 If the density of the linear low density polyethylene and the low density polyethylene is less than 0.93 g / cm3, the slipperiness of the thermoplastic resin layers 11 and 16 decreases. 3 If it exceeds this value, the sealing property of the thermoplastic resin layers 11 and 16 deteriorates.

[0033] The linear low-density polyethylene and the low-density polyethylene have a melt flow rate (MFR) of 0.1 g / 10 min to 10 g / 10 min, preferably 0.2 g / 10 min to 9 g / 10 min, more preferably 1 g / 10 min to 8.5 g / 10 min. The MFR of the linear low-density polyethylene may be lower than the MFR of the low-density polyethylene. The melt flow rate is a value measured by the A method under the conditions of a temperature of 190°C and a load of 21.18 N in the method specified in JIS K7210-1995. When the MFR of the linear low-density polyethylene and the low-density polyethylene is less than 0.1 g / 10 min, an extrusion load is applied during molding. When the MFR of the linear low-density polyethylene and the low-density polyethylene is more than 10 g / 10 min, the resin flows too much, which is not preferable as it causes problems with sealing.

[0034] The biomass polyethylene used was a biomass-derived linear low-density polyethylene manufactured by Braskem (product name: SLL118, density: 0.916 g / cm 3 , MFR: 1.0g / 10min, biomass content 87%), low-density polyethylene derived from biomass manufactured by Braskem (product name: SBC818, density: 0.918g / cm 3 , MFR: 8.1 g / 10 min, biomass content 95%), etc.

[0035] For example, biomass-derived linear low-density polyethylene is produced using sugarcane as a raw material. The polydispersity of such sugarcane-derived linear low-density polyethylene can be 4 or more and 7 or less. On the other hand, the polydispersity of fossil-derived linear low-density polyethylene is usually 1.5 or more and 3.5 or less.

[0036] The outer thermoplastic resin layer 11 is preferably a single layer or a multi-layer containing one or more of the above-mentioned low-density polyethylene derived from fossil fuels or biomass, linear low-density polyethylene, and linear low-density polyethylene using a metallocene catalyst. The outer thermoplastic resin layer 11 can be formed by using one or more of the above-mentioned resins, melt-extruding them using an extruder or the like, and melt-extrusion laminating them on the paper base layer 12. For example, the outer thermoplastic resin layer 11 is a single thermoplastic resin layer containing low-density polyethylene. The thickness of the outer thermoplastic resin layer 11 is, for example, 15 μm or more and 35 μm or less.

[0037] The inner thermoplastic resin layer 16 is preferably a single layer or a multilayer containing one or more of the above-mentioned low-density polyethylene derived from fossil fuels or biomass, linear low-density polyethylene, and linear low-density polyethylene using a metallocene catalyst. The inner thermoplastic resin layer 16 can be formed by using one or more of the above-mentioned resins, producing a resin film or sheet from the resin in advance, and dry laminating the resin film or sheet on the vapor-deposited film 14 via an adhesive layer 15. The thickness of the inner thermoplastic resin layer 16 is, for example, 30 μm to 80 μm, and preferably 40 μm to 60 μm.

[0038] [Paper base layer] The paper base layer 12 functions as a base layer that holds the liquid paper container 100, and is preferably one that can impart strength to the laminate as a packaging product. 2 More than 700g / m 2 Less than 150 g / m 2 More than 600g / m 2 Less than 200 g / m 2 More than 500g / m 2 The paper base layer may be any white paperboard, but from the standpoint of safety, it is preferable to use ivory paper, milk carton base paper, cup base paper, etc., which use natural pulp.

[0039] The paperboard used in the present invention may contain neutral rosin, alkyl ketene dimer, or alkenyl succinic anhydride as a sizing agent, and cationic polyacrylamide, cationic starch, or the like as a fixing agent. It is also possible to use aluminum sulfate to make the paper in a neutral range of pH 6 to 9. In addition to the above sizing agents, the paperboard may contain various papermaking fillers, retention aids, dry strength agents, wet strength agents, binders, dispersants, flocculants, plasticizers, and adhesives as appropriate, in addition to fixing agents.

[0040] [Print layer] The printing layer is a layer on which any desired printed pattern such as letters, numbers, pictures, figures, symbols, patterns, etc. is formed for decoration, display of contents, display of expiration date, display of manufacturer, seller, etc., and for imparting aesthetics. The printing layer can be provided as necessary, for example, on the outer thermoplastic resin layer 11. The printing layer may be provided on the entire surface of the outer thermoplastic resin layer 11, or may be provided on a part of it. The printing layer can be formed using a conventionally known pigment or dye, and the method of forming the printing layer is not particularly limited.

[0041] [Vapor deposition film] As described above, the deposition film 14 has a stretched plastic film 141, a transparent deposition layer 142 provided on the stretched plastic film 141, and a gas barrier coating film 143 provided on the transparent deposition layer 142. Each layer will be described below.

[0042] (Stretched plastic film) The stretched plastic film 141 is a polyester film stretched in a predetermined direction. The stretched plastic film 141 may be a uniaxially stretched film stretched in one predetermined direction, or a biaxially stretched film stretched in two predetermined directions. The stretching direction of the stretched plastic film 141 is not particularly limited. For example, the stretched plastic film 141 may be stretched in the height direction of the liquid paper container formed of the paper container packaging material 10, or may be stretched in the width direction of the liquid paper container.

[0043] The stretched plastic film 141 is a resin composition containing biomass-derived polyester (hereinafter also referred to as biomass polyester). Biomass polyester is a polyester whose diol unit is ethylene glycol derived from biomass and whose dicarboxylic acid unit is dicarboxylic acid derived from fossil fuel. The content of polyethylene terephthalate in the stretched plastic film 141 may be 80% by mass or more, 90% by mass or more, or 95% by mass or more. The stretched plastic film 141 contains, for example, 5% by mass or more of biomass polyester with respect to the entire resin composition of the stretched plastic film 141.

[0044] Since biomass-derived ethylene glycol has the same chemical structure as conventional fossil fuel-derived ethylene glycol, polyester films synthesized using biomass-derived ethylene glycol are comparable in terms of physical properties, such as mechanical properties, to conventional fossil fuel-derived polyester films. Therefore, since the stretched plastic film 141 and the paper container packaging material 10 comprising it have a layer made of a carbon-neutral material, it is possible to reduce the amount of fossil fuel used and the environmental burden compared to stretched plastic films manufactured from raw materials obtained from conventional fossil fuels and paper container packaging materials comprising it.

[0045] Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass such as sugarcane and corn. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.

[0046] The dicarboxylic acid unit of the polyester uses a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid, an aromatic dicarboxylic acid, an aliphatic dicarboxylic acid, and a derivative thereof can be used. As the aromatic dicarboxylic acid, terephthalic acid and isophthalic acid can be mentioned, and as the derivative of the aromatic dicarboxylic acid, a lower alkyl ester of the aromatic dicarboxylic acid, specifically, methyl ester, ethyl ester, propyl ester, butyl ester, etc. can be mentioned. Among these, terephthalic acid is preferable, and as the derivative of the aromatic dicarboxylic acid, dimethyl terephthalate is preferable.

[0047] The resin composition forming the stretched plastic film 141 may contain one or more types of polyester derived from fossil fuels, recycled polyester from polyester products derived from fossil fuels, recycled polyester from polyester products derived from biomass, etc., in a ratio of 5% by mass or more and 45% by mass or less.

[0048] Carbon dioxide in the atmosphere has 14 Since it contains a certain amount of C (105.5pMC), plants that grow by taking in carbon dioxide from the atmosphere, such as corn, 14 The C content is also known to be about 105.5 pMC. In addition, fossil fuels contain 14 It is also known that almost no C is contained in the polyester. Therefore, the total carbon atoms in the polyester are 14By measuring the proportion of C, the proportion of carbon derived from biomass can be calculated.

[0049] The biomass degree can be used as an index representing the ratio of raw materials derived from biomass. In the present embodiment, the "biomass degree" indicates the weight ratio of biomass-derived components. Taking polyethylene terephthalate as an example, since polyethylene terephthalate is a polymer of ethylene glycol containing 2 carbon atoms and terephthalic acid containing 8 carbon atoms in a molar ratio of 1:1, when only biomass-derived ethylene glycol is used, the weight ratio of biomass-derived components in polyethylene terephthalate is 31.25%, so the biomass degree is 31.25% (molecular weight derived from biomass-derived ethylene glycol / molecular weight of one polymerization unit of polyester=60÷192). In polyester derived from fossil fuels, the weight ratio of biomass-derived components is 0%, so the biomass degree of polyester derived from fossil fuels is 0%. In this embodiment, the biomass degree in stretched plastic film 141 is preferably 5.0% or more, and more preferably 10.0% or more, in order to exert the effect as a carbon offset material. In addition, the biomass degree in stretched plastic film 141 may be 30.0% or less, in consideration of problems in the film manufacturing process and physical properties.

[0050] The stretched plastic film 141 can be formed by forming the above-mentioned resin composition into a film by, for example, a T-die method. Specifically, after drying the above-mentioned resin composition, the resin composition is supplied to a melt extruder heated to a temperature (Tm) to Tm+70°C above the melting point of the resin composition to melt the resin composition, and extruded into a sheet from a die such as a T-die, and the extruded sheet is quenched and solidified by a rotating cooling drum or the like to form a film. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, or the like can be used depending on the purpose.

[0051] The film obtained as described above is preferably biaxially stretched. Biaxial stretching can be performed by a conventional method. For example, the film extruded onto the cooling drum as described above is subsequently heated by roll heating, infrared heating, or the like, and stretched in the longitudinal direction to obtain a longitudinally stretched film. This stretching is preferably performed by utilizing the peripheral speed difference between two or more rolls. The longitudinal stretching is usually performed in a temperature range of 50°C or more and 100°C or less. In addition, the longitudinal stretching ratio is preferably 2.5 times or more and 4.2 times or less, depending on the required properties of the film application. If the stretching ratio is less than 2.5 times, the thickness unevenness of the film becomes large, making it difficult to obtain a good film.

[0052] The longitudinally stretched film is then subjected to the sequential processes of transverse stretching, heat setting, and heat relaxation to become a biaxially stretched film. Transverse stretching is usually performed at a temperature range of 50°C to 100°C. The transverse stretching ratio is preferably 2.5 times to 5.0 times, depending on the required properties of the application. If it is less than 2.5 times, the film thickness becomes uneven and it is difficult to obtain a good film, and if it exceeds 5.0 times, breakage is likely to occur during film formation.

[0053] After the transverse stretching, a heat setting treatment is subsequently performed. The preferred temperature range for heat setting is Tg+70 to Tm-10° C. of PET. The heat setting time is preferably 1 to 60 seconds. If a reduction in the heat shrinkage rate is required, a heat relaxation treatment may be performed as necessary.

[0054] The thickness of the stretched plastic film 141 obtained as described above may be any thickness depending on the application. The thickness of the stretched plastic film 141 is, for example, 5 μm or more, and may be 8 μm or more. The thickness of the stretched plastic film 141 is, for example, 100 μm or less, and may be 50 μm or less, 30 μm or less, or 25 μm or less. The range of the thickness of the stretched plastic film 141 can be determined by any combination of the above-mentioned lower limit candidate value and upper limit candidate value. The breaking strength of the film is 5 kgf / mm in the MD direction. 2 More than 40kgf / mm 2Below, 5kgf / mm in TD direction 2 More than 35kgf / mm 2 The elongation at break is 50% or more and 350% or less in the MD direction and 50% or more and 300% or less in the TD direction. The shrinkage percentage when left in a temperature environment of 150°C for 30 minutes is 0.1% or more and 5% or less.

[0055] (Transparent vapor deposited layer) The transparent deposition layer 142 is a thin film of an inorganic oxide containing aluminum oxide as a main component. The transparent deposition layer 142 may contain an aluminum compound such as aluminum oxide or aluminum nitride, carbide, or hydroxide, either alone or in mixtures thereof. Furthermore, the transparent deposition layer 142 may contain an aluminum compound as a main component and further contain a metal oxide such as silicon oxide, silicon nitride, silicon oxynitride, silicon carbide, magnesium oxide, titanium oxide, tin oxide, indium oxide, zinc oxide, or zirconium oxide, or a metal nitride, carbide, or a mixture thereof.

[0056] (Gas barrier coating film) The gas barrier coating film 143 serves to mechanically and chemically protect the transparent deposition layer 142 and improve the barrier properties of the deposition film 14, and is laminated so as to be in contact with the transparent deposition layer 142. The gas barrier coating film 143 is a cured film formed from a coating agent for gas barrier coating films, which is made of a resin composition containing a metal alkoxide, a hydroxyl-containing water-soluble resin, and a silane coupling agent added as necessary.

[0057] The mass ratio of the hydroxyl-containing water-soluble resin to the metal alkoxide in the resin composition is preferably 5 / 95 or more and 20 / 80 or less, and more preferably 8 / 92 or more and 15 / 85 or less. If it is smaller than the above range, the barrier effect of the barrier coating layer tends to be insufficient, and if it is larger than the above range, the rigidity and brittleness of the barrier coating layer tends to be large.

[0058] The thickness of the gas barrier coating film 143 is preferably 100 nm or more and 800 nm or less. If it is thinner than the above range, the barrier effect of the gas barrier coating film 143 is likely to be insufficient, and if it is thicker than the above range, the rigidity and brittleness are likely to be high.

[0059] Metal alkoxides are represented by the general formula R1nM(OR2)m (wherein, R1 and R2 represent a hydrogen atom or an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. Multiple R1s and R2s in one molecule may be the same or different.) (I).

[0060] Specific examples of metal atoms represented by M in the metal alkoxide include silicon, zirconium, titanium, aluminum, tin, lead, borane, and the like. For example, it is preferable to use an alkoxysilane in which M is Si (silicon).

[0061] In the above general formula (I), specific examples of OR2 include alkoxy groups such as a hydroxyl group, a methoxy group, an ethoxy group, an n-propoxy group, an n-butoxy group, an i-propoxy group, a butoxy group, a 3-methacryloxy group, a 3-acryloxy group, and a phenoxy group, and the like.

[0062] In the above, specific examples of R1 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a phenyl group, a p-styryl group, a 3-chloropropyl group, a trifluoromethyl group, a vinyl group, a γ-glycidoxypropyl group, a methacryl group, and a γ-aminopropyl group.

[0063] Specific examples of alkoxysilanes include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, tetrabutoxysilane, tetraphenoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, methyltriphenoxysilane, phenylphenoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, dimethyldiethoxysilane, and diphenyldimethoxysilane. Examples of the alkoxysilane include various alkoxysilanes and phenoxysilanes such as silane, diphenyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-chloropropyltriethoxysilane, trifluoromethyltrimethoxysilane, and 1,6-bis(trimethoxysilyl)hexane. In the present embodiment, condensation polymers of these alkoxysilanes can also be used, and specifically, for example, polytetramethoxysilane, polytetraethoxysilane, etc. can be used.

[0064] The silane coupling agent is used to adjust the crosslink density of the cured film made of the metal alkoxide and the hydroxyl group-containing water-soluble resin, thereby providing the film with barrier properties and resistance to hot water treatment.

[0065] Silane coupling agents have the general formula: R3nSi(OR4)4-n (II) (In the formula, R3 and R4 each independently represent an organic functional group, and n is 1 to 3.) It is expressed as:

[0066] In the above general formula (II), R3 may be, for example, a hydrocarbon group such as an alkyl group or an alkylene group, an epoxy group, a (meth)acryloxy group, a ureido group, a vinyl group, an amino group, an isocyanurate group, or a functional group having an isocyanate group. Specifically, at least one of the two or three R3 is preferably a functional group having an epoxy group, more preferably a 3-glycidoxypropyl group or a 2-(3,4 epoxycyclohexyl) group. Note that R3 may be the same or different.

[0067] In the above general formula (II), R4 is, for example, an organic functional group having 1 to 8 carbon atoms, and is preferably an alkyl group having 1 to 8 carbon atoms or an alkoxyalkyl group having 3 to 7 carbon atoms, which may be branched. For example, examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and a sec-butyl group. Examples of the alkoxyalkyl group having 3 to 7 carbon atoms include a group in which one hydrogen atom has been removed from a straight-chain or branched-chain ether, such as methyl ethyl ether, diethyl ether, methyl propyl ether, methyl isopropyl ether, ethyl propyl ether, ethyl isopropyl ether, methyl butyl ether, ethyl butyl ether, methyl sec-butyl ether, ethyl sec-butyl ether, methyl tert-butyl ether, and ethyl tert-butyl ether. Each of (OR4) may be the same or different.

[0068] Examples of the silane coupling agent represented by the above general formula (II) include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane when n = 1. Examples of the silane coupling agent include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane when n = 2, and 3-glycidoxypropyldimethylmethoxysilane, 3-glycidoxypropyldimethylethoxysilane, 2-(3,4-epoxycyclohexyl)dimethylmethoxysilane, and 2-(3,4-epoxycyclohexyl)dimethylethoxysilane when n = 3.

[0069] In particular, the crosslink density of the cured film of the barrier coating layer using 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane is lower than that of the system using trialkoxysilane. Therefore, the cured film has excellent gas barrier properties and hot water treatment resistance, while also being flexible and has excellent bending resistance, so that the gas barrier properties of the packaging material using the barrier film are unlikely to deteriorate even after the Gelbo flex test.

[0070] The silane coupling agent may be a mixture of those where n=1, 2, or 3, and the ratio of the amounts and the amount of the silane coupling agent used are determined depending on the design of the cured film of the barrier coating layer.

[0071] The hydroxyl-containing water-soluble resin is capable of dehydration co-condensation with the metal alkoxide, and the saponification degree is preferably 90% or more and 100% or less, more preferably 95% or more and 100% or less, and even more preferably 99% or more and 100% or less. If the saponification degree is smaller than the above range, the hardness of the barrier coating layer is likely to decrease.

[0072] Specific examples of the hydroxyl group-containing water-soluble resin include polyvinyl alcohol resins, ethylene-vinyl alcohol copolymers, and polymers of bifunctional phenolic compounds and bifunctional epoxy compounds, each of which may be used alone, or may be used in combination of two or more, or may be used as copolymers. Among these, polyvinyl alcohol is particularly preferred because of its excellent flexibility and affinity, and polyvinyl alcohol resins are suitable.

[0073] Specifically, for example, a polyvinyl alcohol resin obtained by saponifying polyvinyl acetate, or an ethylene-vinyl alcohol copolymer obtained by saponifying a copolymer of ethylene and vinyl acetate can be used. Examples of such polyvinyl alcohol-based resins include PVA-124 (saponification degree = 99%, polymerization degree = 2,400) manufactured by Kuraray Co., Ltd. and GOHSENOL NM-14 (saponification degree = 99%, polymerization degree = 1,400) manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0074] (Preferable structure of vapor-deposited film) Next, a preferred configuration of the vapor-deposited film 14 in the thickness direction will be described with reference to Fig. 5. Fig. 5 shows the results of measuring ions originating from the transparent vapor-deposited layer 142 and ions originating from the stretched plastic film 141 using time-of-flight secondary ion mass spectrometry (TOF-SIMS) while repeatedly soft-etching the surface of the vapor-deposited film 14 on the gas barrier coating film 143 side at a constant speed with a Cs (cesium) ion gun. The transparent vapor-deposited layer 142 of the vapor-deposited film 14 includes a transition region identified by the graph analysis diagram shown in Fig. 5.

[0075] The transition region is a region between a peak position T2 of the element bond Al2O4H transformed into aluminum hydroxide, detected by etching the vapor-deposited film 14 from the gas barrier coating film 143 side using TOF-SIMS, and an interface T1 between the transparent vapor-deposited layer 142 and the stretched plastic film 141. The interface T1 between the transparent vapor-deposited layer 142 and the stretched plastic film 141 is identified as a position where the intensity of the graph of element C6 is half the intensity of element C6 in the stretched plastic film 141. In FIG. 5, the symbol W1 represents the thickness of the transition region.

[0076] The ratio of the thickness W1 of the transition region to the thickness of the transparent vapor deposition layer 142 (hereinafter also referred to as the transformation rate of the transition region) is desirably 5% or more and 60% or less. If the transformation rate exceeds 60%, the adhesion of the transparent vapor deposition layer 142 to the stretched plastic film 141 may decrease when heat is applied to the vapor deposition film 14. In addition, the barrier property of the vapor deposition film 14 against water vapor may decrease. The transformation rate may be 30% or less, 25% or less, or 20% or less. In addition, the transformation rate may be 10% or more, or 15% or more. The range of the transformation rate may be determined by any combination of the above-mentioned lower limit candidate value and upper limit candidate value.

[0077] The interface between the stretched plastic film 141 and the transparent vapor deposition layer 142 is subjected to mechanical and chemical stress due to heat. Therefore, in order to prevent deterioration of adhesion and barrier properties, it is important to firmly cover the stretched plastic film 141 with the transparent vapor deposition layer 142 at the interface between the stretched plastic film 141 and the transparent vapor deposition layer 142.

[0078] Aluminum hydroxide has good adhesion to plastic substrates due to its chemical structure, and because it forms a dense network of its own, it has high water vapor barrier properties. However, the bond structure based on hydrogen bonds between the aluminum hydroxide and the substrate is easily broken down microscopically by heat stress. In addition, water molecules easily penetrate into the film due to the affinity between the grain boundaries of aluminum hydroxide and the aluminum hydroxide network.

[0079] In this embodiment, in order to narrow the transition region formed by aluminum hydroxide in the aluminum oxide vapor-deposited film at the interface with the plastic substrate as much as possible, we focus on the elemental bond Al2O4H and control its abundance to suppress aluminum hydroxide generated from the elemental bond Al2O4H due to thermal stress and increase the ratio of the aluminum oxide film with relatively less aluminum hydroxide, thereby suppressing microscopic destruction of the vapor-deposited film and destruction of the interface with the plastic substrate caused by water molecules due to thermal stress. This makes it possible to provide a vapor-deposited film 14 with unprecedented adhesion and barrier properties.

[0080] The aluminum oxide vapor deposition film can be formed by forming a vapor deposition film on the surface of a plastic substrate that has been pretreated with oxygen plasma. As a vapor deposition method for forming the vapor deposition film, various vapor deposition methods can be applied from among physical vapor deposition and chemical vapor deposition. As a physical vapor deposition method, a method can be selected from the group consisting of vapor deposition, sputtering, ion plating, ion beam assisted method, and cluster ion beam method, and as a chemical vapor deposition method, a method can be selected from the group consisting of plasma CVD, plasma polymerization, thermal CVD, and catalytic reaction type CVD. In this embodiment, the vapor deposition method of physical vapor deposition is preferable.

[0081] A specific example of a method for obtaining the graph in Fig. 5 will be described. First, etching is performed from the outermost surface of the gas barrier coating film 143 using Cs, and analysis is performed on element bonds at the interfaces between the gas barrier coating film 143, the transparent deposition layer 142, and films such as the stretched plastic film 141, and on element bonds in the deposition film. This makes it possible to obtain the graph shown in Fig. 3.

[0082] Next, a specific example of a method for analyzing the graph in Fig. 5 will be described. Here, a case where the gas barrier coating film 143 contains silicon oxide will be described.

[0083] First, in the graph, the position where the strength of SiO2 (mass number 59.96), a constituent element of the gas barrier coating film 143, is half the strength in the gas barrier coating film 143 is identified as the interface between the gas barrier coating film 143 and the transparent vapor deposition layer 142. Next, the position where the strength of C6 (mass number 72.00), a constituent material of the stretched plastic film 141, is half the strength in the stretched plastic film 141 is identified as the interface between the stretched plastic film 141 and the transparent vapor deposition layer 142. In addition, the distance in the thickness direction between the two interfaces is adopted as the thickness of the transparent vapor deposition layer 142.

[0084] Next, the peak representing the measured element bond Al2O4H (mass number 118.93) is obtained, and the region from the peak to the interface is defined as the transition region. However, if the gas barrier coating film 143 is composed of a material with the same mass number as Al2O4H (mass number 118.93), it is necessary to separate the waveform of 118.93.

[0085] When the reactant AlSiO4 and hydroxide Al2O4H are generated at the interface between the gas barrier coating film 143 and the transparent vapor deposition layer 142, they can be separated from the Al2O4H present at the interface between the stretched plastic film 141 and the transparent vapor deposition layer 142. In this way, the separation of the corrugations can be dealt with appropriately depending on the material of the gas barrier coating film 143.

[0086] In waveform separation, for example, a profile of mass number 118.93 obtained by TOF-SIMS is subjected to nonlinear curve fitting using a Gaussian function, and overlapping peaks are separated using the least squares Levenberg-Marquardt algorithm.

[0087] [Adhesive resin layer] The adhesive resin layer 13 is a layer that contains an adhesive resin and bonds the substrate including the paper substrate layer 12 and the film including the vapor-deposited film 14 together.

[0088] As described above, the adhesive resin layer 13 includes the inner adhesive resin layer 131 located on the side of the deposited film 14 and the outer adhesive resin layer 132 located on the side of the paper base layer 12. The inner adhesive resin layer 131 and the outer adhesive resin layer 132 are in contact with each other. The inner adhesive resin layer 131 and the outer adhesive resin layer 132 may be mixed with each other due to the heat applied in the process of bonding the paper base layer 12 and the deposited film 14 together.

[0089] The adhesive resin constituting the inner adhesive resin layer 131 and the outer adhesive resin layer 132 includes a thermoplastic resin. Examples of the thermoplastic resin include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymer polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, methylpentene polymer, polybutene polymer, acid-modified polyolefin resin obtained by modifying a polyolefin resin such as polyethylene or polypropylene with an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, or itaconic acid, polyvinyl acetate resin, poly(meth)acrylic resin, and polyvinyl chloride resin.

[0090] When a polyethylene resin is used as the adhesive resin constituting the inner adhesive resin layer 131 and the outer adhesive resin layer 132, the density is preferably 920 to 970 kg / m because of its excellent heat resistance. 3 The range is preferably 920 to 965 kg / m 3 It is more preferable that the density of the adhesive resin constituting the inner adhesive resin layer 131 and the outer adhesive resin layer 132 is within the above range. When heat is applied to the paper container packaging material 10, the occurrence of pinholes and peeling and wrinkling of the transparent vapor deposition layer 142 can be effectively suppressed. In addition, the occurrence of thermal pinholes caused by heat when producing a liquid paper container can also be suppressed.

[0091] As the adhesive resin constituting the inner adhesive resin layer 131 and the outer adhesive resin layer 132, a polyethylene-based resin is preferable in consideration of the adhesiveness to the paper base layer 12 and the vapor-deposited film 14. Such polyethylene-based resins are ethylene homopolymers, ethylene-α-olefin copolymers, and compositions thereof, and the molecular chain may be linear or may have long-chain branches with 6 or more carbon atoms.

[0092] Examples of the ethylene homopolymer include medium- and low-pressure ethylene homopolymers and high-pressure low-density polyethylenes. Medium- and low-pressure ethylene homopolymers can be obtained by a conventionally known medium- and low-pressure ionic polymerization method. High-pressure low-density polyethylenes can be obtained by a conventionally known high-pressure radical polymerization method.

[0093] Examples of the α-olefin used in the ethylene-α-olefin copolymer include propylene, 1-butene, 4-methyl-1-pentene, 3-methyl-1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene, and one or more of these are used. The method for obtaining the ethylene-α-olefin copolymer is not particularly limited, and examples include high-, medium-, and low-pressure ionic polymerization methods using Ziegler-Natta catalysts, Phillips catalysts, and single-site catalysts. Such copolymers can be conveniently selected from commercially available products.

[0094] As described below, the inner adhesive resin layer 131 is formed on the deposited film 14 by melt extrusion lamination. Two preferable examples of forming the inner adhesive resin layer 131 on the deposited film 14 will be described below.

[0095] [First example] The first example is a form in which an anchor coat layer 17 is provided between the inner adhesive resin layer 131 and the vapor-deposited film 14, as shown in Figures 2 and 4. The anchor coat layer 17 can be a layer made of any resin having a heat-resistant temperature of 135°C or higher, such as a vinyl-modified resin, an epoxy resin, a urethane resin, a polyester resin, or polyethyleneimine. By providing the anchor coat layer 17, the adhesion of the inner adhesive resin layer 131 to the vapor-deposited film 14 can be improved.

[0096] [Second example] The second example is a form in which a resin composition containing one or more compounds selected from the group consisting of epoxy group-containing compounds, silane group-containing compounds, carboxylic acid group-containing compounds, and acid anhydride-containing compounds is used as the adhesive resin of the inner adhesive resin layer 131. For example, a polyethylene-based resin or a polypropylene-based resin can be used. This can reduce the thermal stress that the vapor-deposited film 14 receives in the process of forming the inner adhesive resin layer 131 on the vapor-deposited film 14 by the melt extrusion lamination method. This can suppress the gas barrier property of the vapor-deposited film 14 from decreasing. In addition, even if the anchor coat layer 17 is not provided between the inner adhesive resin layer 131 and the vapor-deposited film 14, the adhesion between the inner adhesive resin layer 131 and the vapor-deposited film 14 can be ensured.

[0097] Examples of the epoxy group-containing compound contained in the adhesive resin constituting the adhesive resin layer 13 include epoxidized vegetable oil (epoxidation of unsaturated double bonds of natural vegetable oil), glycidyl ether type, glycidyl amine type, and glycidyl ester type. Among them, epoxidized vegetable oil is more preferable from the viewpoint of safety when used in food packaging materials. For example, epoxidized soybean oil, epoxidized linseed oil, epoxidized olive oil, epoxidized safflower oil, and epoxidized corn oil are used. The content of such an epoxy group-containing compound is, for example, 0.01 to 10 parts by weight, and preferably 0.01 to 5.0 parts by weight, relative to 100 parts by weight of the adhesive resin constituting the adhesive resin layer 13. If it is less than 0.01 part by weight, the adhesive strength with the vapor deposition film 14 becomes insufficient, and if it exceeds 10 parts by weight, blocking occurs and, particularly when used for food packaging, it is accompanied by an odor, which is not preferable.

[0098] A silane oligomer is preferably used as the silane group-containing compound contained in the adhesive resin constituting the adhesive resin layer 13. More specifically, in order to increase adhesion, a silane oligomer containing any one of an epoxy group, a mercapto group, and an alkoxy group, or several of these groups in the molecule, is desirable. The silane oligomer is blended in an amount of 0.01 to 10 parts by weight, preferably 0.01 to 5 parts by weight, per 100 parts by weight of the adhesive resin constituting the adhesive resin layer 13. If the amount of the silane oligomer is less than 0.01 part by weight, the adhesive strength with the vapor deposition film 14 becomes insufficient, and if it exceeds 10 parts by weight, molding processability becomes poor, which is not preferable.

[0099] The carboxylic acid group-containing compound contained in the adhesive resin constituting the adhesive resin layer 13 may be an ethylene-unsaturated carboxylic acid or a copolymer with an ester thereof. More specifically, an ethylene-acrylic acid copolymer, an ethylene-ethyl acrylate copolymer, an ethylene-methacrylic acid copolymer, or an ethylene-methyl methacrylate copolymer may be used. An ionomer resin in which ethylene-unsaturated carboxylic acid molecules are crosslinked with metal ions may also be used.

[0100] As the acid anhydride-containing compound contained in the adhesive resin constituting the adhesive resin layer 13, maleic acid-modified polyolefin resins such as maleic acid-modified polyethylene resins and maleic acid-modified polypropylene resins are preferred, and maleic anhydride-modified polyolefin resins such as maleic anhydride-modified polyethylene resins and maleic anhydride-modified polypropylene resins are more preferred. Note that the maleic acid-modified polyolefin resins are obtained by graft polymerization of maleic acid to a polyolefin resin.

[0101] The adhesive resin constituting the inner adhesive resin layer 131 and the adhesive resin constituting the outer adhesive resin layer 132 may be the same or different. Examples of combinations of the two are shown in Table 1. Note that the "polyethylene" given as an example of the outer adhesive resin layer 132 is a concept that includes various polyethylenes such as low-density polyethylene, medium-density polyethylene, and high-density polyethylene. [Table 1]

[0102] Next, the thickness of the adhesive resin layer 13 will be described. Preferably, the thickness T1 of the inner adhesive resin layer 131 is thinner than the thickness T2 of the outer adhesive resin layer 132. By reducing the thickness T1 of the inner adhesive resin layer 131, it is possible to suppress deterioration of the characteristics of the transparent vapor deposition layer 142 of the vapor deposition film 14 due to thermal stress during the process of forming the inner adhesive resin layer 131 on the vapor deposition film 14 by the melt extrusion lamination method. In addition, by increasing the thickness T2 of the outer adhesive resin layer 132, it is possible to increase the thickness of the adhesive resin layer 13 as a whole to a degree that can suppress the occurrence of thermal pinholes when molding the liquid paper container.

[0103] The thickness T1 of the inner adhesive resin layer 131 is, for example, 10 μm or more and 25 μm or less, and preferably 10 μm or more and 20 μm or less. The thickness T2 of the inner adhesive resin layer 131 is, for example, less than 1 time, preferably 0.8 times or less, and more preferably 0.6 times or less, the thickness T2 of the outer adhesive resin layer 132. The thickness of the entire adhesive resin layer 13 is, for example, 25 μm or more and 50 μm or less.

[0104] In addition to the various compounds described above, the resin constituting the adhesive resin layer 13 may contain additives commonly used in polyolefin resins, such as antioxidants, light stabilizers, antistatic agents, lubricants, and antiblocking agents, as necessary, within the scope of the present invention.

[0105] [Adhesive layer] The adhesive layer 15 is a layer for adhering a film including the vapor-deposited film 14 and a film including the inner thermoplastic resin layer 16. The adhesive layer 15 may be an adhesive layer or an adhesive resin layer. The adhesive layer and the adhesive resin layer will be described below.

[0106] The adhesive layer can be formed by a conventional method, for example, a dry lamination method. When two layers are bonded by the dry lamination method, the adhesive layer is formed by applying an adhesive to the surface of the film including the deposition film 14 and the film including the inner thermoplastic resin layer 16, whichever is the laminated side, and drying the adhesive. The adhesive to be applied can be, for example, a one-component or two-component cured or non-cured type vinyl, (meth)acrylic, polyamide, polyester, polyether, polyurethane, epoxy, rubber, or other solvent-based, water-based, or emulsion-type adhesive. A two-component cured adhesive can be a cured product of a polyol and an isocyanate compound. The above-mentioned lamination adhesive can be applied by, for example, a direct gravure roll coating method, a gravure roll coating method, a kiss coating method, a reverse roll coating method, a Fountain method, a transfer roll coating method, or other methods.

[0107] The adhesive layer may contain a biomass-derived component. For example, when the adhesive layer contains a cured product of a polyol and an isocyanate compound, at least one of the polyol and the isocyanate compound may contain a biomass-derived component. This can further improve the biomass content of the paper container packaging material 10.

[0108] The adhesive resin layer contains a thermoplastic resin. The adhesive resin layer can be formed by a conventionally known method, for example, a melt extrusion lamination method or a sand lamination method. The thermoplastic resin that can be used for the adhesive resin layer can be a polyethylene resin, a polypropylene resin, or a cyclic polyolefin resin, or a copolymer resin, modified resin, or mixture (including alloy) containing these resins as main components. Examples of polyolefin resins include low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), polypropylene (PP), ethylene-α-olefin copolymers polymerized using metallocene catalysts, random or block copolymers of ethylene and polypropylene, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-maleic acid copolymer, ionomer resins, and acid-modified polyolefin resins obtained by modifying the above-mentioned polyolefin resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid in order to improve adhesion between layers. In addition, resins obtained by graft-polymerizing or copolymerizing unsaturated carboxylic acids, unsaturated carboxylic anhydrides, and ester monomers with polyolefin resins can be used. These materials can be used alone or in combination of two or more. Examples of cyclic polyolefin resins that can be used include cyclic polyolefins such as ethylene-propylene copolymers, polymethylpentene, polybutene, and polynorbornene. These resins can be used alone or in combination of two or more.

[0109] The polyethylene-based resin may be one that uses, as a monomer unit, ethylene derived from biomass as described for the outer thermoplastic resin layer 11 and the inner thermoplastic resin layer 16. This can further improve the biomass content of the paper container packaging material 10.

[0110] Comparing the adhesive layer and the adhesive resin layer described above, the adhesive layer is preferred from the viewpoint of suppressing damage caused by heat to the vapor deposition film in the process of bonding the film including the vapor deposition film 14 and the film including the inner thermoplastic resin layer 16. When an adhesive layer is used as the adhesive layer 15, the transparent vapor deposition layer 142 may be provided on the inner surface of the stretched plastic film 141 as shown in Figures 1 and 2, or may be provided on the outer surface of the stretched plastic film 141 as shown in Figures 3 and 4. When an adhesive resin layer is used as the adhesive layer 15, the transparent vapor deposition layer 142 is preferably provided on the outer surface of the stretched plastic film 141 as shown in Figures 3 and 4.

[0111] <Manufacturing methods for packaging materials> Next, a description will be given of an example of a method for producing the paper container packaging material 10. First, a description will be given of an example of a method for producing the vapor-deposited film 14.

[0112] (Deposition film manufacturing process) First, a stretched plastic film 141 is prepared. Then, a transparent deposition layer 142 containing aluminum oxide is formed on the inner surface of the stretched plastic film 141. Fig. 6 is a diagram showing an example of a film forming apparatus 60. The film forming apparatus 60 and a film forming method using the film forming apparatus 60 will be described below.

[0113] 6, in the film formation apparatus 60, partition walls 85a to 85c are formed in the decompression chamber 62. The partition walls 85a to 85c form a substrate transfer chamber 62A, a plasma pretreatment chamber 62B, and a film formation chamber 62C, and in particular, the plasma pretreatment chamber 62B and the film formation chamber 62C are formed as spaces surrounded by the partition walls and the partition walls 85a to 85c, and each chamber further has an exhaust chamber formed therein as necessary.

[0114] The plasma pretreatment chamber 62B and the plasma pretreatment process in the plasma pretreatment chamber 62B will be described. In the plasma pretreatment chamber 62B, a plasma pretreatment roller 70 is provided to transport the stretched plastic film 141 to be pretreated and to enable plasma treatment, with a portion of the roller 70 being exposed to the substrate transport chamber 62A. The stretched plastic film 141 is transported to the plasma pretreatment chamber 62B while being wound up.

[0115] The plasma pretreatment chamber 62B and the film formation chamber 62C are provided adjacent to the substrate transport chamber 62A, and the stretched plastic film 141 can be moved without being exposed to the atmosphere. The pretreatment chamber 62B and the substrate transport chamber 62A are connected by a rectangular hole, through which a part of the plasma pretreatment roller 70 protrudes to the substrate transport chamber 62A side, and a gap is opened between the wall of the transport chamber and the pretreatment roller 70, and the stretched plastic film 141 can be moved from the substrate transport chamber 62A to the film formation chamber 62C through the gap. The same structure is also formed between the substrate transport chamber 62A and the film formation chamber 62C, and the stretched plastic film 141 can be moved without being exposed to the atmosphere.

[0116] The substrate transport chamber 62A is provided with a winding roller as a winding means for winding up the stretched plastic film 141 having a vapor deposition film formed on one side, which has been moved back to the substrate transport chamber 62A by the film forming roller 75, into a roll, so that the stretched plastic film 141 having the vapor deposition film formed thereon can be wound up.

[0117] When producing a vapor-deposited film 14 having an aluminum oxide vapor-deposited film, the plasma pretreatment chamber 62B is configured to separate the space where plasma is generated from other regions and to efficiently evacuate the opposing space, which facilitates control of plasma gas concentration and improves productivity. The pretreatment pressure formed by reducing the pressure can be set and maintained at about 0.1 Pa to 100 Pa. In particular, the treatment pressure of the oxygen plasma pretreatment to obtain a conversion rate in a preferred transition region of the aluminum oxide vapor-deposited film is preferably 1 Pa to 20 Pa, may be 10 Pa or less, or may be 5 Pa or less. The range of the pretreatment pressure can be determined by any combination of the above-mentioned lower limit candidate value and upper limit candidate value.

[0118] The conveying speed of the stretched plastic film 141 is not particularly limited, but from the viewpoint of production efficiency, it can be at least 200 to 1000 m / min. In particular, a conveying speed of 300 to 800 m / min is preferable for oxygen plasma pretreatment in order to achieve a transformation rate in the transition region of the aluminum oxide vapor deposition film.

[0119] The plasma pretreatment roller 70 constituting the plasma pretreatment device is intended to prevent shrinkage or damage of the stretched plastic film 141 due to heat during plasma treatment by the plasma pretreatment means, and to apply oxygen plasma P uniformly and widely to the stretched plastic film 141. It is preferable that the pretreatment roller 70 can be adjusted to a constant temperature between -20°C and 100°C by adjusting the temperature of a temperature control medium circulating inside the pretreatment roller.

[0120] The plasma pretreatment means includes a plasma supply means and a magnetic forming means, and cooperates with the plasma pretreatment roller 70 to confine oxygen plasma P near the surface of the stretched plastic film 141.

[0121] The plasma pretreatment means is provided so as to cover a part of the pretreatment roller 70. Specifically, the plasma supply means 72 and the magnetic field forming means 73 constituting the plasma pretreatment means are arranged along the surface near the outer periphery of the pretreatment roller 70. The plasma supply means 72 includes a plasma supply nozzle that supplies plasma raw material gas. The magnetic field forming means 73 has a magnet or the like to promote the generation of plasma P. The plasma pretreatment means also has an electrode 71 to which a voltage is applied between the pretreatment roller 70. Note that, in FIG. 6, an example is shown in which the electrode 71 and the plasma supply means 72 are separate members, but this is not limiting. Although not shown, the electrode 71 and the plasma supply means 72 may be configured by an integrated member.

[0122] By generating plasma P in the space between the pretreatment roller 70 and the magnetic forming means 73 and forming an area of ​​high plasma density near the pretreatment roller 70 and the surface of the stretched plastic film 141, oxygen plasma pretreatment can be performed on the inner surface of the stretched plastic film 141 to form a plasma-treated surface.

[0123] The plasma supply means 72 of the plasma pretreatment means includes a raw material volatilization supply device 68 connected to a plasma supply nozzle provided outside the decompression chamber 62, and a raw material gas supply line that supplies raw material gas from the device. The plasma raw material gas supplied is oxygen alone or a mixed gas of oxygen gas and an inert gas, which is supplied from a gas storage section through a flow rate controller while the flow rate of the gas is measured. The inert gas may be one or a mixed gas of two or more types selected from the group consisting of argon, helium, and nitrogen.

[0124] These gases are mixed at a predetermined ratio as necessary to form a plasma raw material gas alone or a mixed gas for plasma formation, which is then supplied to the plasma supply means. The single gas or mixed gas is supplied to the plasma supply nozzle of the plasma supply means, and supplied to the vicinity of the outer periphery of the pretreatment roller 70 where the supply port of the plasma supply nozzle opens. The nozzle opening is directed toward the stretched plastic film 141 on the pretreatment roller 70, and is arranged and configured so that oxygen plasma P can be diffused and supplied uniformly to the entire surface of the stretched plastic film 141. This allows uniform plasma pretreatment to be performed on a large area of ​​the stretched plastic film 141.

[0125] In order to set the conversion rate of the transition region of the aluminum oxide vapor deposition film to 5% or more and 60% or less as described above, the oxygen plasma pretreatment is performed with a mixing ratio of oxygen gas and inert gas (oxygen gas / inert gas) of preferably 1 / 1 or more, and may be 3 / 2.5 or more, or may be 3 / 2 or more. The mixing ratio of oxygen gas and the inert gas (oxygen gas / inert gas) is preferably 6 / 1 or less, and may be 3 / 1 or less, or may be 5 / 2 or less. By setting the mixing ratio to 1 / 1 or more and 6 / 1 or less, the film formation energy of vapor-deposited aluminum on the plastic film increases, and by setting the mixing ratio to 3 / 2 or more and 5 / 2 or less, aluminum hydroxide is formed near the interface of the plastic film, that is, the conversion rate of the transition region decreases. The range of the mixing ratio of oxygen gas and the inert gas (oxygen gas / inert gas) can be determined by any combination of the above-mentioned lower limit candidate value and upper limit candidate value.

[0126] The electrode 71 functions as a counter electrode for the pretreatment roller 70. The plasma raw material gas supplied is excited by a potential difference caused by a high-frequency voltage, a low-frequency voltage, or the like supplied between the electrode 71 and the pretreatment roller 70, and plasma P is generated and supplied.

[0127] Specifically, the electrode 71 is provided with a plasma pretreatment roller as a plasma power source, and an AC voltage with a frequency of 10 Hz to 2.5 GHz is applied between the opposing electrode, and input power control or impedance control or the like is performed to make it possible to apply any voltage between the electrode 71 and the plasma pretreatment roller 70. The film forming device 60 is provided with a power source 82 capable of applying a bias voltage that makes the oxygen plasma P, which can physically or chemically modify the surface properties of the stretched plastic film 141, have a positive potential.

[0128] The plasma intensity per unit area is preferably 50 W·sec / m 2 More than 8000W sec / m 2 Less than 50W·sec / m 2 Below this, no effect of plasma pretreatment was observed, and below 8000W·sec / m 2 Above this level, the stretched plastic film 141 is likely to be deteriorated by the plasma, such as worn out, damaged, discolored, or burned. In particular, the plasma intensity per unit area is 100 W·sec / m 2 The plasma intensity per unit area is preferably 1000W·sec / m 2 Less than 500W·sec / m is preferable. 2 More preferably, it should be less than 300 W·sec / m 2 or less. By applying the above-mentioned plasma intensity with a bias voltage perpendicular to the stretched plastic film 141, it is possible to stably improve the adhesion with the aluminum oxide vapor deposition film, etc. The range of the plasma intensity per unit area can be determined by any combination of the above-mentioned lower limit candidate value and upper limit candidate value.

[0129] The magnetic forming means 73 may be one in which an insulating spacer and a base plate are provided inside a magnet case, and a magnet is provided on the base plate. An insulating shield plate may be provided on the magnet case, and an electrode may be attached to the insulating shield plate. The magnet case and the electrode are electrically insulated, and the electrode can be kept at an electrically floating level even if the magnet case is installed and fixed inside the reduced pressure chamber 62. By providing a magnet, reactivity in the vicinity of the surface of the stretched plastic film 141 is increased, making it possible to form a good plasma pre-treated surface at high speed.

[0130] Preferably, the magnet is configured so that the magnetic flux density at the surface of the stretched plastic film 141 is 10 Gauss to 10,000 Gauss. If the magnetic flux density at the surface of the stretched plastic film 141 is 10 Gauss or more, it becomes possible to sufficiently increase the reactivity in the vicinity of the surface of the stretched plastic film 141, and a good pre-treated surface can be formed at high speed.

[0131] Next, the film formation chamber 62C and the film formation process in the film formation chamber 62C will be described. The film formation apparatus 60 has a film formation roller 75 arranged in the reduced pressure film formation chamber 62C, and a target of a vapor deposition film formation means 74 arranged opposite to the film formation roller 75. The film formation roller 75 wraps and conveys the stretched plastic film 141 with the treated surface of the stretched plastic film 141, which has been pretreated in the plasma pretreatment device, facing outward. In the film formation process, the target of the vapor deposition film formation means 74 is evaporated to form an aluminum oxide film on the surface of the stretched plastic film 141.

[0132] The vapor deposition film forming means 74 is, for example, a resistance heating type, and uses an aluminum metal wire as an evaporation source of aluminum. While supplying oxygen to oxidize the aluminum vapor, an aluminum oxide vapor deposition film is formed on the surface of the stretched plastic film 141.

[0133] The thickness of the transparent deposition layer 142 including the deposition film of aluminum oxide formed as described above is preferably 3 nm or more, may be 8 nm or more, or may be 10 nm or more. The thickness of the transparent deposition layer 142 is preferably 50 nm or less, may be 30 nm or less, may be 20 nm or less, may be 15 nm or less, or may be 14 nm or less. The range of the thickness of the transparent deposition layer 142 can be determined by any combination of the above-mentioned lower limit candidate value and upper limit candidate value. Within this range, the barrier property can be maintained. However, if the deposition film of aluminum oxide is very thin, it becomes difficult to calculate the transformation rate of the transition region by TOF-SIMS measurement.

[0134] Next, a method for forming the gas barrier coating film 143 on the transparent vapor deposition layer 142 will be described. First, the above-mentioned metal alkoxide, a silane coupling agent, a hydroxyl group-containing water-soluble resin, a reaction accelerator (a sol-gel catalyst, an acid, etc.), and an organic solvent such as water as a solvent, or an alcohol such as methyl alcohol, ethyl alcohol, or isopropanol, are mixed to prepare a coating agent for a gas barrier coating film made of a resin composition.

[0135] Next, the above-mentioned gas barrier coating agent is applied onto the transparent deposition layer 142 by a conventional method and dried. This drying step causes the condensation or co-condensation reaction to proceed further, forming a coating film. The above-mentioned coating operation may be further repeated on the first coating film to form multiple coating films consisting of two or more layers.

[0136] Further, the film is heated for 3 seconds to 10 minutes at a temperature in the range of 20 to 200° C., preferably 50 to 180° C., and at a temperature equal to or lower than the softening point of the resin constituting the base layer. This makes it possible to form a gas barrier coating film 143 made of the coating agent for gas barrier coating film on the transparent deposition layer 142. In this way, a deposition film 14 having the stretched plastic film 141, the transparent deposition layer 142, and the gas barrier coating film 143 can be produced.

[0137] Next, a method for manufacturing the paper container packaging material 10 by laminating the vapor-deposited film 14 with other layers and films will be described. Here, a method for manufacturing the paper container packaging material 10 shown in Fig. 2 will be described.

[0138] (Lamination process of inner thermoplastic resin layer) A film constituting the inner thermoplastic resin layer 16 is prepared. When the inner thermoplastic resin layer 16 includes a plurality of layers, the film constituting the inner thermoplastic resin layer 16 is, for example, a coextrusion film produced by coextrusion.

[0139] Next, the vapor-deposited film 14 and the inner thermoplastic resin layer 16 are laminated via the adhesive layer 15 by the dry lamination method. In the dry lamination method, first, an adhesive composition is applied to one of the two films to be laminated. Specifically, the adhesive composition is applied to either the gas barrier coating film 143 constituting the inner surface 14x of the vapor-deposited film 14 or the inner thermoplastic resin layer 16. Preferably, the adhesive composition is applied to the gas barrier coating film 143. Then, the applied adhesive composition is dried to volatilize the solvent. Then, the two films are laminated via the dried adhesive composition. Then, the two laminated films are aged, for example, for 72 hours or more in an environment of 30°C or higher.

[0140] (Inner adhesive resin layer forming process) Also, an anchor coat agent is applied to the outer surface of the deposition film 14, here the surface of the stretched plastic film 141, and dried to form the anchor coat layer 17. Then, a molten adhesive resin is extruded onto the anchor coat layer 17 to form the inner adhesive resin layer 131. As a result, as shown in FIG. 7, a first laminate 20 can be obtained, which has, from the outside to the inside, the inner adhesive resin layer 131, the anchor coat layer 17, the stretched plastic film 141, the transparent deposition layer 142, the gas barrier coating film 143, the adhesive layer 15, and the inner thermoplastic resin layer 16. The inner surface 20x of the first laminate 20 is constituted by the inner thermoplastic resin layer 16, and the outer surface 20y is constituted by the inner adhesive resin layer 131.

[0141] The higher the temperature of the molten adhesive resin, the higher the temperature of the deposition film 14 in contact with the molten adhesive resin. If the temperature of the transparent deposition layer 142 of the deposition film 14 becomes too high, the properties of the transparent deposition layer 142 containing aluminum oxide may deteriorate. For example, the transparent deposition layer 142 may peel off from the stretched plastic film 141, or the gas barrier property of the deposition film 14 may deteriorate. Therefore, in order to suppress deterioration of the properties of the transparent deposition layer 142, it is preferable that the temperature of the molten adhesive resin is low. For example, in the step of forming the inner adhesive resin layer 131, the temperature of the molten adhesive resin is preferably 330° C. or less, and more preferably 320° C. or less.

[0142] The order of the step of laminating the inner thermoplastic resin layer 16 on the inner side of the deposited film 14 and the step of forming the inner adhesive resin layer 131 on the outer side of the deposited film 14 may be arbitrary. Preferably, the step of laminating the inner thermoplastic resin layer 16 on the inner side of the deposited film 14 is carried out first, and then the step of forming the inner adhesive resin layer 131 on the outer side of the deposited film 14 is carried out.

[0143] (Laminating process of the first laminate and the paper base layer) Next, the first laminate 20 and the paper base layer 12 are laminated by sandwich lamination via the outer adhesive resin layer 132. Fig. 8 is a diagram showing a lamination device 90 that laminates the first laminate 20 and the paper base layer 12.

[0144] In the lamination process using the lamination device 90, first, as shown in FIG. 8, the paper base layer 12 is unwound from the first supply roll 91. Also, the first laminate 20 is unwound from the second supply roll 92. Next, the molten adhesive resin 13B for forming the outer adhesive resin layer 132 is extruded between the inner surface of the paper base layer 12 and the inner adhesive resin layer 131 of the first laminate 20. This makes it possible to obtain the second laminate 25 in which the paper base layer 12 and the deposition film 14 of the first laminate 20 are laminated via the adhesive resin layer 13 including the inner adhesive resin layer 131 and the outer adhesive resin layer 132. Note that an anchor coat layer may be provided on the inner surface of the paper base layer 12 before the molten adhesive resin 13B is extruded. This can increase the adhesion between the paper base layer 12 and the outer adhesive resin layer 132. The anchor coat layer may be a layer made of any resin having a heat resistance of 135° C. or higher, such as a vinyl-modified resin, an epoxy resin, a urethane resin, a polyester resin, a polyethyleneimine, etc. The temperature of the adhesive resin 13B in a molten state is preferably 330° C. or lower, more preferably 320° C. or lower.

[0145] Thereafter, in the same line as the lamination device 90, an outer thermoplastic resin layer 11 may be formed on the outer surface of the second laminate 25. For example, as shown in Fig. 8, a molten thermoplastic resin 11A for forming the outer thermoplastic resin layer 11 is extruded onto the outer surface of the paper base layer 12 of the second laminate 25. This makes it possible to obtain a paper container packaging material 10 including the outer thermoplastic resin layer 11, the paper base layer 12, the adhesive resin layer 13, the vapor deposition film 14, the adhesive layer 15 and the inner thermoplastic resin layer 16.

[0146] The advantages provided by the paper container packaging material 10 in this embodiment will be described below.

[0147] In this embodiment, as described above, the adhesive resin layer 13 includes the inner adhesive resin layer 131 located on the side of the vapor-deposited film 14 and the outer adhesive resin layer 132 located on the side of the paper base layer 12. The inner adhesive resin layer 131 is formed on the vapor-deposited film 14 by a melt extrusion lamination method before the step of bonding the vapor-deposited film 14 and the paper base layer 12 by a sandwich lamination method. This reduces the thermal stress that the vapor-deposited film 14 receives, compared with the case where the entire amount of the adhesive resin layer 13 is supplied during the step of bonding the vapor-deposited film 14 and the paper base layer 12 by a sandwich lamination method. This makes it possible to prevent the transparent vapor-deposited layer 142 from peeling off from the stretched plastic film 141 and the gas barrier property of the vapor-deposited film 14 from being deteriorated due to heat. This makes it possible to prevent the barrier property of the vapor-deposited film 14 from being deteriorated, even when aluminum oxide, which is more heat-sensitive than silicon oxide, is used as the transparent vapor-deposited layer 142. Furthermore, by using the aluminum oxide transparent vapor deposition layer 142, a physical vapor deposition method can be adopted as a method for forming the transparent vapor deposition layer 142. This can increase the productivity of the vapor deposition film 14 compared to the case of using a chemical vapor deposition method.

[0148] 8, the anchor coat layer 17 can be formed between the deposited film 14 and the inner adhesive resin layer 131. This can improve the adhesion between the deposited film 14 and the inner adhesive resin layer 131.

[0149] 1 and 2, when the transparent vapor deposition layer 142 of the vapor deposition film 14 is provided on the outer surface of the stretched plastic film 141, when the first laminate 20 including the vapor deposition film 14 and the paper base layer 12 are bonded by the sand lamination method, it is possible to prevent the heat of the molten adhesive resin 13B from reaching the transparent vapor deposition layer 142 of the vapor deposition film 14. This makes it possible to further prevent the transparent vapor deposition layer 142 from peeling off from the stretched plastic film 141 and the gas barrier property of the vapor deposition film 14 from decreasing due to heat.

[0150] <Liquid paper container> The paper container packaging material 10 is used as a material for forming a paper container for liquids. Because the paper container for liquids has excellent barrier properties, it can be suitably used as a paper container for packaging liquids in general, such as alcoholic beverages such as sake, shochu, and wine, dairy beverages such as milk, foods such as soft drinks such as orange juice and tea, and chemical products such as car wax, shampoo, and detergent. Fig. 9 is a perspective view showing an example of a paper container for liquids 100 formed from the paper container packaging material 10.

[0151] The liquid-storing paper container 100 shown in Fig. 9 has a rectangular cylindrical body 101 including sides, a rectangular plate-shaped bottom 102, and an upper portion 103, and is a so-called Gabeltop type container. The upper portion 103 has a pair of opposing inclined plates 104 and a pair of folded portions 105 located between the pair of inclined plates 104 and folded between the inclined plates 104. The pair of inclined plates 104 are bonded to each other by a margin 106 provided at each upper end. A spout may be attached to one of the pair of inclined plates 104, and the spout may be sealed with a cap. A flat-top type container may also be formed. EXAMPLES

[0152] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the description of the following examples as long as it does not depart from the gist of the present invention.

[0153] [Example A1] First, a biomass-derived PET film having a thickness of 12 μm was prepared as the stretched plastic film 141 of the deposited film 14. The biomass-derived PET film was obtained by the following method.

[0154] 83 parts by mass of terephthalic acid derived from fossil fuels and 62 parts by mass of ethylene glycol (manufactured by India Glycol) derived from biomass were subjected to an esterification reaction by a conventional direct polymerization method, and then a condensation polymerization reaction was carried out under reduced pressure to obtain biomass-derived polyethylene terephthalate. Radiocarbon measurement of the obtained biomass-derived polyethylene terephthalate was performed, and the biomass degree by radiocarbon (C14) measurement was found to be 31.25%. 60 parts by mass of the above biomass-derived polyethylene terephthalate, 30 parts by mass of fossil fuel-derived polyethylene terephthalate, and 10 parts by mass of a master batch containing fossil fuel-derived polyethylene terephthalate were fed to an extruder, extruded into a sheet from a T-die, and cooled and solidified by a cooling roll to obtain an unstretched sheet. Next, this unstretched sheet was stretched in the longitudinal direction and then in the transverse direction to obtain a biaxially stretched PET film having a thickness of 12 μm. The biomass content of the obtained biaxially stretched PET film was measured to be 18.8%.

[0155] Next, using the above-mentioned film forming apparatus 60 shown in Figure 6, an oxygen plasma treatment was performed on the surface of the stretched plastic film 141 made of the above-mentioned biaxially stretched PET film, and then a 12 nm thick transparent vapor deposition layer 142 containing aluminum oxide was formed on the oxygen plasma treated surface. (Oxygen plasma pretreatment conditions) Plasma intensity: 150W·sec / m 2 Mixture ratio of oxygen gas and inert gas: oxygen / argon = 2 / 1 Voltage applied between pretreatment drum and plasma supply nozzle: 340V Pretreatment pressure: 3.8Pa (Aluminum oxide film formation conditions) ·Vacuum degree: 8.1×10 -2 Pa -Conveying speed: 400m / min Oxygen gas supply: 20,000sccm

[0156] Subsequently, a gas barrier coating film 143 was formed on the transparent vapor deposition layer 142. Specifically, first, 385 g of water, 67 g of isopropyl alcohol, and 9.1 g of 0.5N hydrochloric acid were mixed and adjusted to a pH of 2.2, and 175 g of tetraethoxysilane as a metal alkoxide and 9.2 g of glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed into the solution while cooling it to 10° C. to prepare solution A. Solution B was prepared by mixing 14.7g of polyvinyl alcohol with a degree of polymerization of 2400 and a saponification value of 99% or more as a water-soluble polymer, 324g of water, and 17g of isopropyl alcohol. Solution A and solution B were mixed in a weight ratio of 6.5:3.5 to obtain a solution used as a coating agent for gas barrier coating films. The above-prepared gas barrier coating agent was applied onto the above-mentioned transparent deposition layer 142 by spin coating. Thereafter, the film was heated in an oven at 180° C. for 60 seconds to form a gas barrier coating film 143 having a thickness of about 400 nm on the transparent deposition layer 142. In this manner, a deposition film 14 having the stretched plastic film 141, the transparent deposition layer 142, and the gas barrier coating film 143 was obtained.

[0157] [Example A2] Except for changing the thickness of the transparent vapor deposition layer 142 to 10 nm, the transparent vapor deposition layer 142 was formed on the stretched plastic film 141 in the same manner as in Example A1, and a gas barrier coating film 143 was formed on the transparent vapor deposition layer 142. In this manner, a vapor deposition film 14 having the stretched plastic film 141, the transparent vapor deposition layer 142, and the gas barrier coating film 143 was obtained.

[0158] [Example A3] Except for changing the thickness of the transparent vapor deposition layer 142 to 14 nm, the transparent vapor deposition layer 142 was formed on the stretched plastic film 141 in the same manner as in Example A1, and a gas barrier coating film 143 was formed on the transparent vapor deposition layer 142. In this manner, a vapor deposition film 14 having the stretched plastic film 141, the transparent vapor deposition layer 142, and the gas barrier coating film 143 was obtained.

[0159] [Reference example A1] Except for changing the thickness of the transparent vapor deposition layer 142 to 7 nm, the transparent vapor deposition layer 142 was formed on the stretched plastic film 141 in the same manner as in Example A1, and a gas barrier coating film 143 was formed on the transparent vapor deposition layer 142. In this manner, a vapor deposition film 14 having the stretched plastic film 141, the transparent vapor deposition layer 142, and the gas barrier coating film 143 was obtained.

[0160] [Reference example A2] Except for not performing the oxygen plasma pretreatment, a transparent deposition layer 142 was formed on a stretched plastic film 141, and a gas barrier coating film 143 was formed on the transparent deposition layer 142 in the same manner as in Example A1. In this manner, a deposition film 14 having the stretched plastic film 141, the transparent deposition layer 142, and the gas barrier coating film 143 was obtained.

[0161] [Reference example A3] A transparent deposition layer 142 was formed on a stretched plastic film 141, and a gas barrier coating film 143 was formed on the transparent deposition layer 142 in the same manner as in Example A1, except that the mixing ratio of oxygen gas and inert gas in the oxygen plasma treatment was oxygen / argon = 4 / 1. In this manner, a deposition film 14 having the stretched plastic film 141, the transparent deposition layer 142, and the gas barrier coating film 143 was obtained.

[0162] [Reference example A4] A transparent deposition layer 142 was formed on a stretched plastic film 141, and a gas barrier coating film 143 was formed on the transparent deposition layer 142 in the same manner as in Example A1, except that the pretreatment pressure in the oxygen plasma treatment was set to 50 Pa. In this manner, a deposition film 14 having the stretched plastic film 141, the transparent deposition layer 142, and the gas barrier coating film 143 was obtained.

[0163] [Reference example A5] The plasma intensity in oxygen plasma treatment was 1200W·sec / m 2Except for the above, a transparent vapor deposition layer 142 was formed on a stretched plastic film 141, and a gas barrier coating film 143 was formed on the transparent vapor deposition layer 142 in the same manner as in Example A1. In this manner, a vapor deposition film 14 having the stretched plastic film 141, the transparent vapor deposition layer 142, and the gas barrier coating film 143 was obtained.

[0164] The conversion rate of the vapor-deposited films 14 of the above-mentioned Examples A1 to A3 and Reference Examples A1 to A4 was measured. The color of the vapor-deposited films 14 of the above-mentioned Example A1 and Reference Example A5 was measured. The oxygen permeability and water vapor permeability of the film laminates including the vapor-deposited films 14 of the above-mentioned Examples A1 to A3 and Reference Examples A1 to A2 were measured.

[0165] (Metamorphic rate) While repeatedly soft-etching the surface of the gas barrier coating film 143 of the deposition film 14 at a constant speed with a Cs (cesium) ion gun, ions originating from the gas barrier coating film 143, ions originating from the transparent deposition layer 142, and ions originating from the stretched plastic film 141 were measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS). As a result, a graph was obtained in which the unit of the vertical axis (intensity) is the intensity of the measured ions and the unit of the horizontal axis (cycle) is the number of etching cycles, as shown in FIG. 5 above.

[0166] The time-of-flight secondary ion mass spectrometer used in the TOF-SIMS was a TOF.SIMS5 manufactured by ION TOF, Inc., and measurements were performed under the following measurement conditions. (TOFSIMS measurement conditions) Primary ion type: Bi3++ (0.2pA, 100μs), measurement area: 150×150μm 2 Et gun type: Cs (1 keV, 60 nA), Et area: 600 x 600 μm 2 , Et rate: 3sec / cycle In the analysis, it is important to distinguish the ions derived from aluminum oxide from those derived from other components, to select ions with sufficient strength, and in particular to obtain a depth distribution that can be approximately converted to the concentration distribution of the elemental bond Al2O4H. Taking these factors into consideration, Cs ions were selected as the ion gun for measuring the ions derived from aluminum oxide, which were the subject of the measurement.

[0167] Using Cs, etching was performed from the outermost surface of the gas barrier coating film 143, and analysis was performed on elemental bonds at the interfaces between the gas barrier coating film 143, the transparent deposition layer 142, and the stretched plastic film 141, and on elemental bonds in the deposition film, and a graph of the measured elements and elemental bonds was obtained. In the graph, the position where the strength of SiO2 (mass number 59.96), a constituent element of the gas barrier coating film 143, is half the strength in the gas barrier coating film 143, was specified as the interface between the gas barrier coating film 143 and the transparent deposition layer 142. In addition, the position where the strength of C6 (mass number 72.00), a constituent material of the stretched plastic film 141, is half the strength in the stretched plastic film 141, was specified as the interface between the stretched plastic film 141 and the transparent deposition layer 142. In addition, the distance in the thickness direction between the two interfaces was adopted as the thickness of the transparent deposition layer 142.

[0168] Next, the peak representing the measured element bond Al2O4H (mass number 118.93) was obtained, and the region from the peak to the interface was defined as the transition region. However, if the gas barrier coating film 143 is composed of a material with the same mass number as Al2O4H (mass number 118.93), it is necessary to separate the waveform of 118.93.

[0169] When the reactant AlSiO4 and hydroxide Al2O4H are generated at the interface between the gas barrier coating film 143 and the transparent vapor deposition layer 142, they can be separated from the Al2O4H present at the interface between the stretched plastic film 141 and the transparent vapor deposition layer 142. In this way, the separation of the corrugations can be dealt with appropriately depending on the material of the gas barrier coating film 143.

[0170] In waveform separation, for example, a profile of mass number 118.93 obtained by TOF-SIMS is subjected to nonlinear curve fitting using a Gaussian function, and overlapping peaks are separated using the least squares Levenberg-Marquardt algorithm.

[0171] The transformation rate of the transparent vapor-deposited layer 142 of the vapor-deposited films 14 of Examples A1 to A3 and Reference Examples A1 to A4 was calculated as (thickness W1 of the transition region / thickness of the transparent vapor-deposited layer 142)×100(%). The results are shown in FIGS. 10A and 10B.

[0172] (Color) Using a spectrophotometer (manufactured by Konica Minolta, Inc. [model name: CM-700d]), the L* value, a* value, and b* value in the L*a*b* color system were measured for one measurement sample (stretched plastic film 141 / transparent deposition layer 142 / gas barrier coating film 143) made from the deposition film 14. The results are shown in Figures 10A and 10B.

[0173] (Oxygen permeability and water vapor permeability) A 70 μm thick non-stretched polypropylene film (CPP film) and a 15 μm thick stretched nylon film were bonded together by a dry lamination method via a two-component curing polyurethane adhesive to prepare a laminate. In addition, a two-component curing polyurethane adhesive was applied to the gas barrier coating film 143 side of the deposition film 14 of Examples A1 to A3 and Reference Examples A1 to A2, and a drying treatment was performed to form an adhesive layer on the gas barrier coating film 143. Next, a laminate including the CPP film and the stretched nylon film was bonded to the deposition film 14 via the adhesive layer on the gas barrier coating film 143 of the deposition film 14 by a dry lamination method to prepare a film laminate for evaluation. The layer structure of the film laminate is expressed as follows, from the outside to the inside. PET film / transparent vapor deposition layer / gas barrier coating / adhesive layer / stretched nylon film / adhesive layer / CPP film

[0174] A sample for measuring oxygen permeability was prepared using the film laminate for evaluation. Specifically, the film laminate for evaluation was first subjected to aging treatment at 36° C. for 48 hours, and then cut out from the film laminate for evaluation to prepare a sample.

[0175] Next, the five types of measurement samples of Examples A1 to A3 and Reference Examples A1 to A2 were set so that the stretched plastic film 141 made of a PET film was the oxygen supply side, and the oxygen permeability was measured in accordance with JIS K 7126 B method under measurement conditions of 23°C and 90% RH atmosphere. The measurement device used was an oxygen permeability measurement device (manufactured by Modern Control (MOCON) [model name: OX-TRAN 2 / 21]). The results are shown in Figures 10A and 10B.

[0176] (Water vapor permeability) The water vapor permeability was measured using the same samples as those used for measuring the oxygen permeability. Specifically, each measurement sample was set so that the stretched plastic film 141 was on the sensor side, and the water vapor permeability was measured in accordance with JIS K 7126 B method under measurement conditions of 40°C and 100% RH atmosphere. A water vapor permeability measuring device (a measuring device manufactured by MOCON [model name: PERMATRAN 3 / 33]) was used as the measuring device. The results are shown in Figures 10A and 10B.

[0177] As shown in FIG. 10A, in the deposition films 14 of Examples A1 to A3, the conversion rate of the transition region of the transparent deposition layer 142 was in the above-mentioned range of 5% to 60%, specifically, in the range of 10% to 25%. As the thickness of the transparent deposition layer 142 increased, the conversion rate tended to decrease. On the other hand, in the deposition films 14 of Reference Examples A1 to A2, the element-bonded Al2O4 HThe peaks were too small to separate, so the conversion rate in the transition region could not be calculated. In addition, in the vapor-deposited films 14 of Reference Examples A3 and A4, the plasma discharge was not stable, and plasma pretreatment was not possible, so the conversion rate in the transition region could not be calculated. For these reasons, in order to produce a vapor-deposited film 14 such that the conversion rate in the transition region of the transparent vapor-deposited layer 142 is in the range of 5% to 60%, it is preferable to satisfy all of the following manufacturing conditions I to IV. Manufacturing conditions I The transparent deposition layer has a thickness of 8 nm or more. Manufacturing conditions II The mixture ratio of oxygen gas to inert gas in the oxygen plasma treatment is 3 / 2.5 or more and 3 / 1 or less. Manufacturing conditions III The pretreatment pressure in the oxygen plasma treatment is 1 Pa or more and 20 Pa or less. Manufacturing conditions IV The plasma intensity in oxygen plasma treatment is 100W·sec / m 2 More than 500W sec / m 2 The following is the result.

[0178] 10A and 10B, the b* value of the deposited film 14 of Reference Example A5 was larger than the b* value of the deposited film 14 of Example A1. In addition, in the deposited film 14 of Reference Example A5, coloration of the stretched plastic film 141 was visually confirmed. The above-mentioned production conditions I to IV are considered to be useful in suppressing coloration.

[0179] As shown in FIG. 10A, the film laminates including the deposited films 14 of Examples A1 to A3 had oxygen permeabilities of 0.5 cc / m 2 / 24hr / atm or less, and the water vapor permeability is 0.4g / m 2 On the other hand, as shown in FIG. 10B, in the sample of the film laminate including the deposited film 14 of Reference Example A2, the oxygen permeability was 0.8 cc / m 2 / 24hr / atm, and water vapor permeability is 1.1g / m 2From these findings, it can be said that oxygen plasma pretreatment is effective in maintaining the barrier properties against gases such as oxygen and water vapor.

[0180] [Example B1] As the deposited film 14, a deposited film 14 produced in the same manner as in Example A1 was prepared.

[0181] A polyethylene film having a thickness of 60 μm was prepared as the inner thermoplastic resin layer 16. Next, the surface of the vapor-deposited film 14 facing the gas barrier coating film 143 was laminated via the adhesive layer 15 to the polyethylene film by dry lamination.

[0182] In addition, after the anchor coat layer 17 was provided on the stretched plastic film 141 of the deposition film 14, the inner adhesive resin layer 131 was formed on the anchor coat layer 17 by melt extrusion lamination. Specifically, the molten adhesive resin constituting the inner adhesive resin layer 131 was extruded onto the anchor coat layer 17 at a temperature of 320°C and a thickness of 20 μm. The adhesive resin was 0.923 g / cm 3 A low-density polyethylene having a density of 1000 nm and a melt flow rate (MFR) of 3.6 g / 10 min or less was used. In this manner, a first laminate 20 shown in FIG.

[0183] In addition, as the paper base layer 12, a liquid base paper (basis weight 385 g / m 2 ) was prepared. Next, an anchor coat layer was formed on the inner surface of the base paper for liquid, and then the base paper for liquid and the first laminate 20 were laminated via the outer adhesive resin layer 132 by the sand lamination method using the above-mentioned lamination device 90 shown in Fig. 8. Specifically, the molten adhesive resin constituting the outer adhesive resin layer 132 was extruded between the base paper for liquid and the stretched plastic film 141 of the first laminate 20 at a temperature of 320°C and a thickness of 30 µm. Low-density polyethylene was used as the adhesive resin.

[0184] Next, an anchor coat layer was formed on the outer surface of the liquid base paper, and then molten polyethylene resin was extruded to form an outer thermoplastic resin layer 11. In this way, a paper container packaging material 10 shown in Figure 2 was obtained.

[0185] The layer structure of the paper container packaging material 10 of this embodiment is expressed as follows. PE25 / AC / Paper / AC / PE30 / PE20 / AC / PET12 / Vapor deposition / Barrier / DL / PEF60 "PE" means extruded polyethylene layer. "AC" means anchor coat layer. "Paper" means paper base layer. "PET" means PET film. "Vapor deposition" means aluminum oxide film. "Barrier" means gas barrier coating film. "DL" means adhesive layer. "PEF" means polyethylene film. Numbers indicate layer thickness (unit: μm).

[0186] [Example B2] A packaging material 10 for paper containers was produced in the same manner as in Example B1, except that the thickness of the inner adhesive resin layer 131 was set to 12 μm and the thickness of the outer adhesive resin layer 132 was set to 15 μm.

[0187] The layer structure of the paper container packaging material 10 of this embodiment is expressed as follows. PE25 / AC / Paper / AC / PE15 / PE12 / AC / PET12 / Vapor deposition / Barrier / DL / PEF60

[0188] [Example B3] A packaging material 10 for paper containers was produced in the same manner as in Example B2, except that a transparent vapor deposition layer 142 of the vapor deposition film 14 was provided on the outer surface of the stretched plastic film 141, and a gas barrier coating film 143 was provided on the transparent vapor deposition layer 142.

[0189] The layer structure of the paper container packaging material 10 of this embodiment is expressed as follows. PE25 / AC / paper / AC / PE15 / PE12 / AC / barrier / vapor deposition / PET12 / DL / PEF60

[0190] [Comparative Example B1] A paper container packaging material 10 was produced in the same manner as in Example B1, except that the thickness of the inner adhesive resin layer 131 was set to 30 μm and the thickness of the outer adhesive resin layer 132 was set to 30 μm.

[0191] The layer structure of the paper container packaging material 10 of this embodiment is expressed as follows. PE25 / AC / Paper / AC / PE30 / PE30 / AC / PET12 / Vapor deposition / Barrier / DL / PEF60

[0192] [Comparative example B2] A laminate was prepared in the same manner as in Example B1, in which the deposited film 14 and the inner thermoplastic resin layer 16 were laminated together. Next, in a state in which the anchor coat layer and the inner adhesive resin layer were not provided on the stretched plastic film 141 of the deposited film 14, a molten adhesive resin was extruded between the laminate in which the deposited film 14 and the inner thermoplastic resin layer 16 were laminated together and the paper base layer 12 at a temperature of 320°C and a thickness of 20 μm to laminate the two together. The adhesive resin was 0.923 g / cm 3 A low density polyethylene having a density of 0.01 to 0.15 and a melt flow rate (MFR) of 3.6 g / 10 min or less was used.

[0193] Next, an anchor coat layer was formed on the outer surface of the liquid base paper, and then molten polyethylene resin was extruded to form an outer thermoplastic resin layer 11. In this way, a paper container packaging material 10 was produced.

[0194] The layer structure of the paper container packaging material 10 of this comparative example is expressed as follows. PE25 / AC / paper / AC / PE20 / PET12 / vapor deposition / barrier / DL / PEF60

[0195] The layer structures of the paper container packaging materials 10 of Examples B1 and B2 and Comparative Examples B1 and B2 are shown in FIG.

[0196] For the paper container packaging materials 10 of Examples B1 to B3 and Comparative Examples B1 and B2, the peel strength, water vapor permeability, and oxygen permeability were measured, and an evaluation of the filling machine sealability was performed.

[0197] (peel strength) For each of the paper container packaging materials 10 of Examples B1 to B3 and Comparative Examples B1 and B2, the interlayer peel strength (N / 15 mm) between the adhesive resin layer 13 and the vapor-deposited film 14 was measured. Specifically, a 90° peel test was performed at a peel speed of 50 mm / min using a tensile tester (Tensilon universal testing machine RTC1310A, manufactured by Orientec Co., Ltd.). The results are shown in Figure 12.

[0198] (Water vapor permeability) For each of the paper container packaging materials 10 of Examples B1 to B3 and Comparative Examples B1 and B2, the water vapor transmission rate was measured at a temperature of 40° C. and a humidity of 100% RH using a measuring device (model name: PERMATRAN) manufactured by MOCON, Inc. in the United States, in accordance with JIS K 7129 (number of samples: N=10). The results are shown in FIG.

[0199] (Oxygen permeability) For each of the paper container packaging materials 10 of Examples B1 to B3 and Comparative Examples B1 and B2, oxygen transmission rates were measured at a temperature of 23° C. and a humidity of 90% RH using a measuring device (model name: OXTRAN) manufactured by MOCON, Inc. in the United States, in accordance with JIS K 7126 (number of samples: N=10). The results are shown in FIG.

[0200] (Filling machine sealability) The paper container packaging materials 10 of Examples B1 to B3 and Comparative Examples B1 to B2 were molded and heat-sealed to produce liquid paper containers. The heat-sealing temperature was 260°C, 280°C, 300°C, 320°C, or 340°C. The obtained liquid paper containers were filled with water to evaluate whether water leaked. The heat-sealed areas were visually checked for pinholes. The results are shown in FIG. 13. In FIG. 13, "good" means that no water leaked and no pinholes were generated at the heat-sealed areas. "bad" means that delamination occurred in the paper container packaging material 10 when the paper container packaging material 10 was molded and heat-sealed.

[0201] As can be seen from the comparison between Examples B1 to B3 and Comparative Example B1, by making the thickness of the inner adhesive resin layer 131 smaller than that of the outer adhesive resin layer 132, for example, 20 μm or less, it was possible to ensure the water vapor barrier property and the oxygen barrier property. 2 It was possible to reduce it to less than one day.

[0202] As can be seen from a comparison between Examples B1 to B3 and Comparative Example B2, by providing the anchor coat layer 17 on the outer surface of the vapor-deposited film 14, the adhesion between the vapor-deposited film 14 and the adhesive resin layer 13 was improved and peel strength was ensured. Specifically, the peel strength was made 3 N / 15 mm or more. In addition, interlayer peeling of the paper container packaging material 10 during the production of a liquid paper container was suppressed. [Explanation of symbols]

[0203] 10 Packaging materials for paper containers 11 Outer thermoplastic resin layer 12 Paper base layer 13 Adhesive resin layer 131 Inner adhesive resin layer 132 Outer adhesive resin layer 14 Deposition film 141 Stretched plastic film 142 Transparent vapor deposition layer 143 Gas barrier coating film 15 Adhesive layer 16 Inner thermoplastic layer 17 Anchor coat layer 20 Laminate 90 Stacking device 91 First supply roll 92 Second supply roll 100 liquid paper containers

Claims

1. A packaging material for paper containers comprising, in order from outside to inside, at least an outer thermoplastic resin layer, a paper base layer, an adhesive resin layer, a vapor deposition film, an adhesive layer, and an inner thermoplastic resin layer, the deposition film comprises a stretched plastic film, a transparent deposition layer containing aluminum oxide provided on the stretched plastic film, and a gas barrier coating film provided on the transparent deposition layer; the stretched plastic film of the vapor-deposited film contains a biomass-derived polyester, The adhesive resin layer includes polyethylene, the adhesive layer contains a cured product of a polyol and an isocyanate compound, the adhesive resin layer includes an inner adhesive resin layer located on the vapor-deposited film side and an outer adhesive resin layer located on the paper base layer side, The thickness of the adhesive resin layer is 27 μm or more and 50 μm or less, The thickness of the inner adhesive resin layer is 2 / 3 to 4 / 5 times the thickness of the outer adhesive resin layer, The paper container packaging material further includes an anchor coat layer located between the inner adhesive resin layer and the vapor deposition film, The packaging material for paper containers, wherein the anchor coat layer is made of a vinyl modified resin, an epoxy resin, a urethane resin or a polyester resin.

2. The packaging material for paper containers according to claim 1 , wherein the thickness of the inner adhesive resin layer of the adhesive resin layer is 10 μm or more and less than 25 μm.

3. The packaging material for paper containers according to claim 1 , wherein the transparent vapor deposition layer of the vapor deposition film is provided on an inner surface of the stretched plastic film.

4. The packaging material for paper containers according to claim 1 , wherein the transparent vapor deposition layer of the vapor deposition film is provided on an outer surface of the stretched plastic film.

5. the transparent deposition layer includes a transition region; The transition region is a region of elemental bond Al that is transformed into aluminum hydroxide, which is detected by etching the vapor-deposited film from the gas barrier coating film side using time-of-flight secondary ion mass spectrometry (TOF-SIMS). 2 O 4 the region between the position of the peak of H and the interface between the transparent deposition layer and the stretched plastic film, The packaging material for paper containers according to any one of claims 1 to 4, wherein the ratio of the thickness of the transition region to the thickness of the transparent vapor deposition layer is 5% or more and 60% or less.

6. The packaging material for paper containers according to any one of claims 1 to 5, wherein the outer thermoplastic resin layer or the inner thermoplastic resin layer contains polyethylene derived from biomass.

7. A liquid paper container made from the paper container packaging material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Paper container for liquid

    JP2002154532A

  • Paper container for liquid

    JP2008143585A

  • Barrier film, and laminate film and package made from the same

    JP2015036208A

  • Laminate equipped with polyester resin layer and packing product equipped with the same

    JP2018001611A